Synthesis of Some New 2-Cyanoamino-4-Thio-5 and 6-Substituted-Amino 4,5-Dihydro-S-Triazines, Part-I - Tayade, D.T. (Asian Journal of Chemistry, 2010)
In the present work, synthesis of some 2-cyanoamino-4-thio, 5 and6-substituted amino 4,5-dihydro 5-triazines are described.